A SOCIO-ECONOMIC STUDY OF FISHERMEN IN POHE VILLAGE, HULONTHALANGI DISTRICT, GORONTALO CITY - Nurul Aprilia Huraira; Helman Manay; Naufal Raffi Arrazaq; Irvan Tasnur (Satmata: Journal of Historical Education Studies, 2026)
This study aims to examine the social and economic conditions of fishermen in Pohe Village, Hulonthalangi Sub-district, Gorontalo City. Using a descriptive qualitative approach, the research explores the everyday realities of fishermen, including income patterns, social structure, family roles, and the challenges they encounter. The findings reveal that fishermen live in unstable economic conditions, relying heavily on daily catches and fluctuating market prices, with limited access to education, technology, and institutional support. Nevertheless, the fishing community exhibits strong social solidarity, significant female involvement in household economies, and resilience through livelihood diversification and the preservation of local cultural values. Environmental issues and lack of structural support further contribute to their vulnerability. Therefore, a community-based, participatory, and sustainable empowerment strategy is essential to improve their overall well-being. This study highlights the need to view fishermen not as passive recipients of aid, but as vital actors in coastal development.